Students' View of Causes, Forms and Solutions of Lecturers' Involvement in Corrupt Practices in Tertiary Educational Institutions, Kwara State Nigeria - Shofiu Adewuyi Rasheed (Universitas Majalengka, 2023)
This descriptive survey investigated students' views on lecturers' engagement in corrupt practices within Kwara State's tertiary educational institutions in Nigeria. The study targeted NCE. Three-level students, with 150 respondents randomly sampled using stratified and purposive techniques from public Colleges of Education. A researcher-designed questionnaire was used, addressing four research questions. Mean and standard deviation analyzed the data, revealing a high level of lecturer involvement in Corruption. Causes cited included greed, students' disinterest in learning, weak enforcement of anti-corruption laws, and lecturer intimidation. Corrupt practices identified encompassed money extortion from students, sexual harassment, score manipulation, forcing `handout purchases, and certificate forgery. Proposed solutions included timely salary payments, robust anti-corruption groups, funding lecturers' international conferences, strict sanctions against wrongdoers, and merit-based recruitment and promotion. These findings emphasize the need to combat Corruption, preserve institutional integrity, and create a conducive learning atmosphere. Implementation of effective anti-corruption measures can promote ethical academic conduct, ensuring transparent and accountable educational systems. Further research and practical interventions are vital to curb Corruption's impact on Nigeria's educational sector.